Improving Academic Integration Values Through Project-Based Citizenship Education Learning - Delfiyan Widiyanto; Annisa Istiqomah; Hari Wahyono; Novitasari Novitasari; Mashud Syahroni (Indonesian Journal of Education and Learning, 2026)
The purpose of this study was to determine the improvement of students' attitude aspects after taking part in project-based Citizenship Education courses. Citizenship education aims to form good citizens and have the skills of ideal young citizens. As a form of improving the skills of young citizens with education in a formal environment, it has a greater impact on the internalization of values. This study uses a quasi-experimental research type (quasi-experimental design). This study uses a quasi-experimental design without a control or comparison class. The experimental design used is one group pre-test-post-test. The results of the study show that project-based learning can improve attitudes towards academic integrity values. These values ​​are in the form of honesty, trust, fairness, respect, responsibility, and humility. Students' responses to project-based learning are easy and they really like the learning that is carried out. However, the improvement in attitudes towards academic integrity values ​​has not been maximized in all indicators, especially in the values ​​of honesty and respect. In order to be able to increase all values ​​to the maximum, a more comprehensive project learning evaluation is needed.